Successful Pregnancy and Childbirth in a Patient with Diabetic Kidney Disease Receiving Hemodialysis - Kim, Young Il; Jung, Hee Jae; Kim, Jeoung Hoon; Kim, Yeo-Joo; Kim, Yun Sook; Lee, Eun Young (Soonchunhyang medical science, 2012)
Pregnancy outcomes for women uncontrolled diabetes mellitus are poor. Women with chronic kidney disease and end-stage renal disease, if pregnant, will develop pregnancy-related complications. In the case of severe renal failure and diabetes mellitus, the incidence of prematurity, low birth weight, and neonatal death increases. Despite these risks, there have been few reported cases of successful pregnancy outcomes for these women. Adherence to a schedule of strict glucose monitoring, blood pressure and volume control, correction of anemia, and intensive hemodialysis may play important roles in the management of these women. Successful pregnancy and childbirth in a patient with diabetic kidney disease receiving hemodialysis have not been previously reported in Korea, to our knowledge. Herein, we report a case of a successful pregnancy outcome in a patient with diabetic end-stage renal disease undergoing hemodialysis. KCI Citation Count: 0